Pergeseran Aksara dan Kebertahanan Bahasa Minangkabau dalam Tradisi Tafsir Ulama Minangkabau - Fithrah Lathifah; Ahmad Baidowi (LPPM IIQ An Nur Yogyakarta, 2026)
This study explores the shift of script and the endurance of the Minangkabau language in the Qur’anic exegesis tradition of Minangkabau scholars during the twentieth century as a historical and cultural phenomenon. The transition from Jawi to Latin script represents not only a technical change in writing but also an epistemological transformation from the exclusive surau tradition to the modern madrasa and print-based public sphere. The study aims to explain the process of this script shift, the persistence of Minangkabau linguistic elements in Latin-script tafsir, and its implications for reading traditions, interpretation, and religious authority. Employing a qualitative, descriptive-historical approach through library research, the analysis focuses on five primary tafsirs: al-Burh?n, al-Qaul al-Bay?n, al-Da?wah wa al-Irsy?d, Tafsir Qur’an Karim, and Tafsir al-Azhar. Findings reveal that the Jawi script symbolized the scholarly authority of traditional ulama, while the Latin script expanded public accessibility and transformed intellectual authority into a more inclusive form. Despite the shift in medium, Minangkabau diction and idioms persisted as local expressions of Qur’anic understanding, maintaining the continuity of Islamic values within a cultural framework. In conclusion, Minangkabau Qur’anic exegesis reflects a dialogue between tradition and modernity, emphasizing language and script as markers of Islamic intellectual identity in the Indonesian archipelago.